Singapore private international law: Commercial issues and practice - CHONG, Adeline (Institutional Knowledge at Singapore Management University, 2023)
There has been significant reform in Singapore private international law in recent years. Developments such as the establishment of the Singapore International Commercial Court, the incorporation of the Hague Convention on Choice of Court Agreements into Singapore law, and the enactment of the Insolvency, Restructuring and Dissolution Act 2018, have all thrown the country into a period of rapid growth.Singapore Private International Law: Commercial Issues and Practice provides a roadmap to assist readers in navigating this changing landscape. In it, Chong and Yip offer an overview of Singapore's legal system, exploring how governmental and judicial efforts have capitalised on Singapore's location at the heart of Asia, its status as a leading financial centre globally, and its modern infrastructure, to make it the hub of choice for cross-border disputes and insolvency andrestructuring efforts. Practical guidance is given to matters such as changes to jurisdiction, protective measures, the recognition and enforcement of foreign judgments, general choice of law issues, and issues specific to contract, tort, unjust enrichment, equitable obligations, trusts, property, corporations, andinternational insolvency and corporate restructuring. The book also looks at how the English common law principles have been implemented and developed in Singapore, with relevant cases, legislation, and foreign sources used to offer a comparative perspective.